2015
DOI: 10.4068/cmj.2015.51.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of Depression with Physical Disorders: Research and Clinical Implications

Abstract: Depression is prevalent in patients with physical disorders, particularly in those with severe disorders such as cancer, stroke, and acute coronary syndrome. Depression has an adverse impact on the courses of these diseases that includes poor quality of life, more functional impairments, and a higher mortality rate. Patients with physical disorders are at higher risk of depression. This is particularly true for patients with genetic and epigenetic predictors, environmental vulnerabilities such as past depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
129
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(132 citation statements)
references
References 90 publications
(100 reference statements)
1
129
0
2
Order By: Relevance
“…This comorbidity can easily lead to disability, such as in the workplace [18,19], and high health care costs [20]. In such cases of comorbidity, the treatment response is often less favourable for both the chronic medical condition [21] and the mental disorder [22][23][24]. Research has shown that CC is effective, as compared to CAU, in improving depressive and anxiety disorders [25][26][27][28][29][30][31][32][33], and the National Institute for Health and Care Excellence (NICE) guidelines on depression recommend CC as the treatment of choice in the case of concomitant chronic medical disorders [34].…”
Section: Protocol Registration Numbermentioning
confidence: 99%
“…This comorbidity can easily lead to disability, such as in the workplace [18,19], and high health care costs [20]. In such cases of comorbidity, the treatment response is often less favourable for both the chronic medical condition [21] and the mental disorder [22][23][24]. Research has shown that CC is effective, as compared to CAU, in improving depressive and anxiety disorders [25][26][27][28][29][30][31][32][33], and the National Institute for Health and Care Excellence (NICE) guidelines on depression recommend CC as the treatment of choice in the case of concomitant chronic medical disorders [34].…”
Section: Protocol Registration Numbermentioning
confidence: 99%
“…41 Integrated models of primary and mental health care are designed to enhance acceptability and availability of mental health services and enable collaborative care to address both physical and mental health needs.…”
Section: Integrated Care Models In Culturally Diverse Populationsmentioning
confidence: 99%
“…The government of India estimates, in its MH policy, that 2 out of 10 Indians are likely to suffer from some form of mental illness by the year 2020 (2). Depression has been linked to common conditions that present to the Emergency Department (ED) such as cardio-vascular illnesses, stroke, COPD, diabetes, chronic kidney disease, and cancer (3)(4)(5)(6)(7)(8)(9). As such, the prevalence of depression was found to be higher in ED patients when compared to the general population (10).…”
Section: Introductionmentioning
confidence: 98%